Inherited anxiety-related parent–infant dyads alter LHPA activity. (2nd January 2019) - Ullmann, E.; Licinio, J.; Perry, S. W.; White, L. O.; Klein, A. M.; Barthel, A.; Petrowski, K.; Stalder, T.; Oratovski, B.; von Klitzing, K.; Bornstein, S. R.; Kirschbaum, C.
Abstract: The pathogenesis of post-traumatic stress disorder (PTSD) is incompletely understood. We hypothesize that disruptions in mother-child relations may be a key contributor to development of PTSD. A normal and healthy separation-individuation process requires adaptations of self- and interactive contingency in both the mother and her child, especially in early childhood development. Anxious mothers are prone to overprotection, which may hinder the individuation process in their children. We examined long-term stress hormones and other stress markers in subjects three generations removed from the Holocaust, to assess the long-term consequences of inherited behavioral and physiological responses to prior stress and trauma. Jewish subjects who recalled overprotective parental behavior had higher hairsteroid-concentrations and dampened limbic-hypothalamic-pituitary-adrenal (LHPA) axis reactivity compared to German and Russian-German subjects with overprotective parents. We suggest that altered LHPA axis activity in maternally overprotected Jewish subjects may indicate a transmitted pathomechanism of "frustrated individuation" resulting from cross-generational anti-Semitic experiences. Thus measurements of hairsteroid-concentrations and parenting practices may have clinical value for diagnosis of PTSD. We propose that this apparent inherited adaptivity of LHPA axis activity could promote higher individual stress resistance, albeit with risk of an allostatic overload.